Shifting From Passive Quality Reporting to Active Nudging to Influence Consumer Choice of Health Plan. (August 2020) - Haviland, Amelia M.; Damberg, Cheryl L.; Mathews, Megan; Paddock, Susan M.; Elliott, Marc N.
Comparative quality information on health plan and provider performance is increasingly available in the form of quality report cards, but consumers rarely make use of these passively provided decision support tools. In 2012-2013, the Centers for Medicare & Medicaid Services (CMS) initiated quality-based nudges designed to encourage beneficiaries to move into higher quality Medicare Advantage (MA) plans. We assess the impacts of CMS' targeted quality-based nudges with longitudinal analysis of 2009-2014 MA plan enrollment trends. Nudges are associated with 17% reductions in enrollment in the lowest-performing plans and 3% increases in enrollment in the highest performing plans (annually, p < .01 for both), occurring at the time of nudge implementation and relative to trends for plans with moderate performance that were not targeted by nudges. These findings suggest that quality-based nudges can successfully steer consumers into higher quality plans and provide opportunities for purchasers and payers to increase consumers' use of quality information.